TINDAK TUTUR ILOKUSI DALAM WACANA KRITIS PENDIDIKAN: KAJIAN PRAGMATIK PADA VIDEO YOUTUBE FERRY IRWANDI: Tindak tutur ilokusi, pragmatik, wacana digital, YouTube, pendidikan - Nabilla Alya Wardhani; Eko Suroso; Laily Nurlina; Isnaeni Praptanti (UNIVERSITAS PGRI YOGYAKARTA, 2026)
This study is designed to identify and describe the variety of illocutionary speech acts found in a YouTube video titled “The Reasons for the Failure to Adopt the Finnish Education System in Indonesia,” a video published by Ferry Irwandi on October 10, 2024. This study focuses on language use in digital critical discourse that addresses issues of national education policy. The method applied in this research is a descriptive qualitative approach. Data collection was conducted through listening accompanied by note-taking, while the data analysis phase relied on the determinant element sorting technique a method of interpreting data by considering the context of the utterance, the speaker’s intent, and relevant theoretical frameworks. Based on the findings, all five categories of illocutionary speech acts were present in the video with varying frequencies, totaling 14 utterances. Among these five categories, the assertive speech act appeared most frequently with 4 utterances, followed by the directive with 3 utterances, the expressive with 3 utterances, while the commissive and declarative each accounted for 2 utterances. The results of this study provide a tangible contribution to the development of pragmatic studies, particularly in the context of digital-based communication, while also offering deeper insight into the illocutionary strategies commonly employed by independent content creators in conveying ideas to a broad audience.This study is expected to improve the public’s pragmatic literacy in understanding educational content on social media.